The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/682197
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroabietic Acid Derivative QC2 Induces Oncosis in Hepatocellular Carcinoma Cells

Abstract: Aim. Rosin, the traditional Chinese medicine, is reported to be able to inhibit skin cancer cell lines. In this report, we investigate the inhibitory effect against HCC cells of QC2, the derivative of rosin's main components dehydroabietic acid. Methods. MTT assay was used to determine the cytotoxicity of QC2. Morphological changes were observed by time-lapse microscopy and transmission electron microscopy and the cytoskeleton changes were observed by laser-scanning confocal microscopy. Cytomembrane integrity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Several forms of nonapoptotic and nonautophagic cell death, such as oncosis 7 , necroptosis 8 , entosis 9 , anoikis 10 , and programmed necrosis 11 , have been described according to specific cellular and molecular criteria. Importantly, two similar types of nonapoptotic and nonautophagic cell death: cytoplasmic vacuolation death and paraptosis have been described based on the specific formation of cytoplasmic vacuoles 12 13 14 .…”
mentioning
confidence: 99%
“…Several forms of nonapoptotic and nonautophagic cell death, such as oncosis 7 , necroptosis 8 , entosis 9 , anoikis 10 , and programmed necrosis 11 , have been described according to specific cellular and molecular criteria. Importantly, two similar types of nonapoptotic and nonautophagic cell death: cytoplasmic vacuolation death and paraptosis have been described based on the specific formation of cytoplasmic vacuoles 12 13 14 .…”
mentioning
confidence: 99%
“…Researches focusing on the synthesis and evaluation of new DHA derivatives are emerging in recent years. Many derivatives of DHA have been reported to have the property of inhibiting cancer cells and bacteria [ 9 12 ]. We demonstrated in the present work that the DHA derivative QC4 exerted strong cytotoxicity on gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The ultramicrostructural analysis of QC4-treated cells was conducted following published protocols [ 12 ]. The ultrathin sections were obtained, stained with 1% toluidine blue, and observed by a transmission electron microscope (JEM-1010, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, in the in vitro cytotoxic assay, two compounds (QC2 and QC4) ( Figure 2) of these derivatives exhibited significant antiproliferative activity against hepatocarcinoma and gastric cancer cell lines with IC 50 values at low micromolar level. In pharmacological studies, it was found that QC2 could activate oncosis related protein calpain to induce the damage of cytomembrane and organelles which finally lead to oncosis in hepatocarcinoma cells 36 . QC4 could also induce the oncosis and apoptosis in gastric cancer cells 37 .…”
Section: Introductionmentioning
confidence: 99%